KETERLIBATAN MASYARAKAT DALAM PENGEMBANGAN OBJEK WISATA PANTAI TERHADAP SOSIAL EKONOMI DAN BUDAYA DI PULAU PANJANG KECAMATAN SUNGAI BEREMAS KABUPATEN PASAMAN BARAT PROVINSI SUMATERA BARAT - Irsyadul Fikri; Yoskar Kadarisman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Pulau Panjang Village Beach Tourism Object, since it began to be developed in 2012, has experienced various developments carried out by related agencies in seeking improvement in Pulau Panjang Beach Tourism Object. The development carried out has the aim to increase attractiveness and improve the socio economic economy of the community. Community involvement in the development of tourist objects is very necessary in the course of the course of a development, community involvement in the development of tourist objects affects the socio-economic and cultural life of Pulau Panjang village communities. This research uses a descriptive method with a quantitative approach in which the data that has been obtained in the field will be processed in the form of tables and do a picture. The results in this study indicate the level of community involvement in the development of Pulau Panjang beach attractions in the moderate category with a rate of 62.3% based on field data. While the impact caused by the development of tourism on Pulau Panjang tends to have a positive effect with the benefit of increased income increases, provide business opportunities and side jobs, broaden horizons, perspectives, understandings, interactions, and introduce the area to the public outside, enough to cover all the shortcomings caused by tourism activities. Keywords: Participation, Tourism Objects, Impact